The Effect of Using German-Language Films on Improving Students' Hörverstehen - Tania, Nurul; Navira, Afifah; Ramadhani, Wusti Alya; Siagian, Theresia; Sari, Risnovita (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
German is one of the foreign languages ??studied in Indonesia, but listening skills (Hörverstehen) are often considered the most difficult part to master. This problem arises from the distinctive accents of native speakers, the high speaking speed, and the use of words not always found in textbooks. This study aims to determine the extent to which the use of German-language films can help improve students' listening skills. The method used was a review of five previous relevant studies. The review results indicate that German-language films can have a positive impact on improving listening skills. This can aid comprehension of the material, while expanding vocabulary and increasing enthusiasm for learning. Furthermore, films help create a more creative, enjoyable, and contextual learning environment. Thus, German-language films can be considered an effective learning tool, especially when used actively and appropriately to students' abilities.